Projekty infrastrukturalne w kształtowaniu funkcji logistycznych województwa pomorskiego - Droździecki, Sławomir (Infrastructure Projects in the Shaping of Logistic Functions Within the Pomeranian Province, 2008)
Gdańsk Pomerania is one of the socio-geographical regions of Poland. Administrative regulations locate the Pomorskie voivodship in the comparative localization on the south shave of the Baltic Sea. That is a crucial factor to define the economic character of this area. The general analysis of the basic economic and social parameters shows this region as "average" in Poland in terms of social growth, welfare, strength of the economy, level of education, etc. The most important and characteristic feature is the existence of huge economic and social differences within the capital and the provincial territory of the region. Generally almost the whole economic and social potential is concentrated in a relatively small area, conglomerate of tree cities of Sopot, Gdańsk and Gdynia. The fundament of the economic power of this agglomeration is the existence of maritime ports of Gdynia and Gdańsk and the close by located cooperating companies as: shipyards, sea and sea-land carriers, multimodal transport operators, forwarders and logistic operators. The general assumption is that the transport is a crucial element of the region's strength and potential. The main task for this article is to show what the importance of transport for the Gdańsk is Pomerania and what the expectations for the future growth and development of the transport infrastructure of this part of Poland could be.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 236-255